The Role of Purchase Intention in Mediating Content Marketing and E-Wom on Product Purchase Decision - Sahya Amertha, Genijayendra; Setini , Made; Putra , Ida Bagus Udayana; Faizan Ul-Haq , Faizan Ul-Haq (Journal of Sustainable Economic and Business, 2025)
Objectives: This study aims to analyze the role of Purchase Intention as a mediating variable in the relationship between Content Marketing and Electronic Word of Mouth (E-WOM) on Purchase Decisions for Bata shoe products in Denpasar. Methodology: This study uses a quantitative method with a population of individuals who have seen marketing content or Bata shoe advertisements in Denpasar. A sample of 100 respondents was selected using a purposive sampling technique, referring to the Hair formula. Data analysis was carried out using SEM-PLS (Structural Equation Modeling - Partial Least Square). Finding: The results of this study indicate that content marketing has a positive and significant effect on purchasing decisions. Content marketing has a positive but insignificant effect on purchasing intention. E-WOM has a positive but insignificant effect on purchasing decisions. E-WOM has a positive and significant effect on purchasing intention. Purchasing intention has a positive and significant effect on purchasing decisions. Content marketing has a positive and insignificant effect on purchasing decisions through purchasing intention. Purchasing intention does not mediate (unmediated). E-WOM has a positive and significant effect on purchasing decisions through purchasing intention. Purchasing intention mediates fully (full mediation).  Conclusion: Improving Content Marketing, E-WOM, and Purchase Intention strategies consistently and interactively can increase the Purchase Decision of Bata shoe products. Especially, Purchase Intention has an important role as a full mediator in the influence of E-WOM on purchasing decisions.